Novelirani pravni instituti pri podjetnikih, osebnih družbah in družbah z omejeno odgovornostjo - Prelič, Saša (Podjetje in delo, 2015)
Important legislative goal, implemented with the amendments to the Slovenian Companies Act (ZGD-1I), is also the reduction of unfair business practice, primarily in limited liability companies. Therefore certain new legal instruments have been introduced in order to tackle such unfair practice and to strengthen creditors' protection.
Keywords: dolgovi; družbe z omejeno odgovornostjo; podjetniki; pravno varstvo; terjatve; upniki